Comparison of the assessment of the level of sexual education in secondary schools by adolescents and parents - Skonieczna, Joanna; Olejniczak, Dominik; Kielan, Aleksandra (Journal of Education, Health and Sport, 2017)
Introduction: Sexualiy education is one of the elements of sexual health promotion. In Poland sexuality education is conducted in the form of a Preperation for family life subject. The subject deviate from established standards in the curriculum, and from WHO recommendations. Objective: The assesment of the opinion and expectations of secondary school students and their parents on the school-based sexual education. Material and Methods: The study covered a total of 340 students and 108 parents. Two questionnaires were used. The IBM SPSS Statistics 21.0 package from Predictive Solutions was used in the calculations. Results: Approximately 94% of students and 96% of parents perceive knowledge of sexuality as important. The most commonly mentioned sources of knowledge of students about sexuality were colleagues (62%) and Internet (61%). Nearly half of adolescents does not feel that, as a result of the Preperation for family life subject, has gained valuable information. Conclusions: It is important to undertake actions aimed at fulfilling the obligation to run the sexuality education to applicable legal regulations and adapting the curriculum to recommendations of the WHO, preparing the teachers in order to ensure the hight quality of the teaching and providing the evidence-based knowledge.